Expert Consensus on the Use of On‐Demand Treatments for OFF Episodes in Parkinson's Disease: A Modified Delphi Panel. Issue 4 (11th March 2023) - Isaacson, Stuart H.; Achari, Madhureeta; Bhidayasiri, Roongroj; Comella, Cynthia; Farmer, Jill Giordano; Gupta, Fiona; Jones, Sarah; Kreitzman, David; Kremens, Daniel; Lewis, Simon J.G.; Poewe, Werner; Tolosa, Eduardo; et al.
ABSTRACT: Background: On‐demand treatments can treat OFF episodes in Parkinson's disease, however, there is limited information regarding when to prescribe them. Objective: Develop expert consensus to determine appropriate clinical factors for considering on‐demand treatments. Methods: Using a RAND/UCLA modified Delphi panel method, a panel developed consensus on the use of on‐demand treatments for OFF episodes. Results: The panel agreed on‐demand treatments were appropriate when OFF episodes were associated with greater functional impact and interfered with basic daily activities. The panel also agreed on‐demand treatment may be appropriate for patients with morning akinesia and/or delayed ON of first levodopa dose and >1 type of OFF episode (eg, early morning OFF or wearing OFF regardless of frequency). Conclusions: Experts agreed on‐demand treatment is appropriate for many patients with OFF episodes. The greater the functional impact of OFF episodes, the more likely experts agreed that on‐demand treatment is appropriate to prescribe.